EXCHANGE RATE FLUCTUATIONS ON THE BALANCE OF PAYMENTS IN THE IRAQI ECONOMY - M.D. Kawthar Muhammad Dehaim Hassan (Scholar Express Journals, 2023)
The Iraqi economy is a rentier economy that depends mainly on the oil sector for its exports, and through those exports it is possible to obtain hard currency, which is the US dollar, which has a significant impact on the Iraqi balance of payments, and thus the extent of its impact on the volume of foreign trade represented by the amount of imports and exports and oil exports. It represents a large percentage of more than 98% of total exports, and through these exports it is possible to obtain hard currency, which is the US dollar, which has a significant impact on the Iraqi balance of payments. Therefore, the importance of research becomes clear in clarifying the path that exchange rates lead in their effects on the balance of payments. As for the problem of the research, it shows the extent of the impact of exchange rates on the balance of payments, which is characterized by between rise and fall, meaning that it is experiencing a state of economic instability. The research has concluded that the Iraqi balance of payments is greatly affected by the volume of oil revenues. When there is a rise or decline in the quantity of oil exports, it is reflected This is in the form of a surplus or deficit in the balance of payments.
Keywords: Exchange rates; balance of payments; oil revenues